Mycobacterium tuberculosis spoligotypes and drug-resistant characterization from Beira compared to genotypes circulating in Mozambique - Lívia Maria Pala Anselmo; Emilyn Costa Conceição; Evangelina Namburete; Cinara Feliciano; Silvana Spindola; Christophe Sola; Valdes Roberto Bollela (Revista da Sociedade Brasileira de Medicina Tropical, 2019)
Abstract INTRODUCTION Mozambique is one of three countries with high prevalence of tuberculosis (TB), TB/human immunodeficiency virus coinfection, and multidrug-resistant TB. We aimed to describe Mycobacterium tuberculosis spoligotypes circulating among drug resistant (DR) strains from Beira, Mozambique comparing them with genotypes in the country. METHODS: We performed spoligotyping of 79 M. tuberculosis suspected of DR-TB compared all spoligotype patterns published on the international database and PubMed. RESULTS: Both in Beira and Mozambique (n=578), the main clades were Latin-American-Mediterranean, East-African-Indian, Beijing and T, with no extensively DR TB cases. CONCLUSIONS: Beira and Mozambique share the same population genetic structure of M. tuberculosis.